Inframalleolar bypass for chronic limb-threatening ischemia. (April 2021) - Benedetto, Filippo; Spinelli, Domenico; Pipitò, Narayana; Barillà, David; Stilo, Francesco; De Caridi, Giovanni; Barillà, Chiara; Spinelli, Francesco
The aims of this study were to analyze the results of inframalleolar bypass for chronic limb-threatening ischemia (CLTI) and to identify outcome-predicting factors. All consecutive patients undergoing inframalleolar bypass for CLTI between 2015 and 2018 were included in this retrospective, single-center study. Outflow artery was the most proximal patent vessel segment in continuity with inframalleolar arteries. Bypasses originating from the popliteal artery were defined as 'short bypasses'. Sixty patients underwent inframalleolar bypass, with four patients undergoing bilateral procedures, making a total of 64 limbs included. The mean age was 73 ± 14 and 52 (81%) were male. The great saphenous vein was the preferred conduit ( n = 58, 91%), in a devalvulated fashion ( n = 56, 88%). Superficial femoral artery was the most common inflow artery for 'long' grafts ( n = 22, 34%), while popliteal artery was the inflow artery for all 'short' grafts ( n = 25, 39%). Dorsalis pedis artery was chosen as an outflow artery in 41 patients (63%). Median follow-up was 21 months. Two-year primary and secondary patency, limb salvage, amputation-free survival, and overall survival rates were 67 ± 6%, 88 ± 4%, 84 ± 4%, 72 ± 6%, and 85 ± 4%, respectively. At multivariate analysis, dialysis was an independent predictor for poor primary patency (HR, 4.6; 95% CI, 1.62–13.05; p = 0.004), whereas a short bypass was independently associated with an increased primary patency (HR, 0.3; 95% CI, 0.10–0.89; p = 0.03). In conclusion, bypass grafting to the inframalleolar arteries resulted in good patency rates, limb salvage and overall survival. Dialysis patients had lower primary patency but still had good limb salvage and survival. Short bypass was a predictor of improved primary patency.